Volume 5: Fusion Engineering; Student Paper Competition; Design Basis and Beyond Design Basis Events; Simple and Combined Cycle 2012
DOI: 10.1115/icone20-power2012-54841
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Liquid Dispersion in the Packed-Bed by Electrical Resistance Tomography

Abstract: Revealing gas-liquid permeable flow phenomena in the porous media is helpful for the environmental impact assessment of geological disposal of radioactive waste and purification of radioactive contamination water. This paper aims to investigate the liquid phase dispersion inside co-current downward gas-liquid flow in the bed packed with spherical particle as basic model. Water and air are injected from the top center of column, and water is spreading to the entire cross-section flowing down along the column. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Relative error between ERT and CFD is used to evaluate the uniformity. Since a true value cannot be obtained here, the denominator of relative error is replaced by a larger value between x ERT and x CFD as equation (15). erefore, the relative error is still in a range from 0% to 100% and negative values will not appear.…”
Section: E Distribution Under Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative error between ERT and CFD is used to evaluate the uniformity. Since a true value cannot be obtained here, the denominator of relative error is replaced by a larger value between x ERT and x CFD as equation (15). erefore, the relative error is still in a range from 0% to 100% and negative values will not appear.…”
Section: E Distribution Under Differentmentioning
confidence: 99%
“…Mcmanus et al [14] have investigated the distribution of only a single liquid phase under different flow rates in TBR by ERT. en, Eda et al [15] have investigated the gas-liquid flow distribution of spherical particles in the packed bed by ERT and found that the liquid flow rate has an influence on the radial diffusion of liquid phase.…”
Section: Introductionmentioning
confidence: 99%